2020
DOI: 10.1007/s00784-020-03264-x
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic treatment patterns in the very old: an insurance database analysis from Northeast Germany

Abstract: Objectives We assessed dental prosthetic services utilization in very old Germans. Methods A comprehensive sample of 404,610 very old (≥ 75 years), insured at one large statutory insurer (Allgemeine Ortskrankenkasse Nordost, acting in the federal states Berlin, Brandenburg, Mecklenburg-Vorpommern), were followed over 6 years (2012-2017). Our outcome was the utilization of prosthetic services, in total and seven subgroups: (1) Crowns/partial crowns, (2) fixed dental prostheses (FDPs), (3) partial removable pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 28 publications
4
12
0
1
Order By: Relevance
“…Fifth, we assessed the impact of social hardship status on utilization. Hardship status is a proxy for low income but does otherwise not directly impact on accessibility of dental care in Germany except for prosthetic care (where additional costs are decreased when having this status; this was found with an increased utilization in the investigated cohort) [5]. In line with previous research, hardship status was found to be associated with decreased utilization, possibly acting as marker of not only low income but also low health literacy and unfavorable health behaviors.…”
Section: F62bsupporting
confidence: 83%
“…Fifth, we assessed the impact of social hardship status on utilization. Hardship status is a proxy for low income but does otherwise not directly impact on accessibility of dental care in Germany except for prosthetic care (where additional costs are decreased when having this status; this was found with an increased utilization in the investigated cohort) [5]. In line with previous research, hardship status was found to be associated with decreased utilization, possibly acting as marker of not only low income but also low health literacy and unfavorable health behaviors.…”
Section: F62bsupporting
confidence: 83%
“…Such status is a proxy for low income. It has been found associated with increased utilization of prosthetic services, as individuals with this status usually pay very low or no additional fee at all for any prosthetic service; that is, financial utilization barriers for this type of dental treatment are very low or absent [7]. For the present analysis, hardship status was used only as a social marker, as the analyzed dental services (examination, restorations, surgery, prevention, outreach care) are coming at no costs for all statutorily insured individuals, regardless of their age.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study and building on claims data, we found a disparate utilization of prosthetic services in the very old, with those aged 85 years or older, those living rural, and those with severe general health conditions utilizing prosthetic services, by large, to a lower degree than younger, urban living and only limitedly sick seniors [7]. The only service the former group used more often was maintenance of existing prosthetics.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…La demencia se clasifica como: "Una enfermedad de carácter neurodegenerativo, que involucra la alteración de múltiples funciones corticales superiores, acompañadas por un deterioro del control emocional, del comportamiento social o de la motivación, que se han agrupado como síntomas en tres dimensiones: cognitiva, funcional y del comportamiento 25 .…”
Section: Manejo De La Salud Bucal En Paciente Geriátrico Con Demenciaunclassified